PERILAKU BERBUSANA REMAJA PUTRI PADA SAAT PERSEMBAHYANGAN DI PURA AGUNG WANA KERTHA JAGATNATHA KOTA PALU - Irmayanti Diah Jatiningsih; I Gede Suhartawan (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2020)
The purpose of this study are, knowing the behavior of female teenage dress attitudes at the Agung Wana Kertha Jagatnatha Temple Palu City and knowing the factors that influence the behavior of the teenage girl dressing during prayers at Agung Wana Kertha Jagatnatha Temple Palu City, and the impact of dress behavior teenage girl during prayers at the Agung Wana Kertha Jagatnatha Temple Palu City. The design of this study uses qualitative methods. The target of the study is young women aged 18-21 years. The research instrument was in the form of indepth interview. Data research techniques in this study were observation, interviews, and documentation. The qualitative data analysis technique in this study uses the Creswell data analysis technique. Test the validity of using triangulation. The results showed that female teenage dress behavior during prayers at the Agung Wana Kertha Jagatnatha Temple palu city was more likely to use custom clothing that had been modified. personal, as well as wrong parental behavior in wearing custom clothing. The impact caused by female teenage dress behavior during prayer at Agung Wana Kertha Jagatnatha temple, Palu City, disturbs the opposite sex concentration during praying at the temple and can cause jealousy and grouping among young women, because not everyone can afford kebaya’s modification.